High prevalence of neutralizing antibodies after long-term botulinum neurotoxin therapy. (1st January 2019) - Albrecht, Philipp; Jansen, Alexander; Lee, John-Ih; Moll, Marek; Ringelstein, Marius; Rosenthal, Dietmar; Bigalke, Hans; Aktas, Orhan; Hartung, Hans-Peter; Hefter, Harald
Abstract : Objective: To investigate the prevalence of neutralizing antibodies (NAbs) against botulinum neurotoxin type A (BoNT/A) during long-term BoNT/A treatment in different neurologic indications. Methods: In this monocentric, observational cross-sectional study, 596 outpatients treated with BoNT/A for different indications were tested for BoNT/A binding antibodies by ELISA. Positive samples were investigated for NAbs with the mouse hemidiaphragm test. The prevalence of NAbs was analyzed for different indications: facial hemispasm, blepharospasm, cervical dystonia, other dystonia, and spasticity. Besides the rate of NAb-positive patients overall and per patient subgroup, a Kaplan-Meier analysis of the probability of remaining NAb negative with duration of treatment is provided, and a stepwise binary logistic regression analysis is performed to identify factors significantly contributing to the induction of NAbs. Results: Overall, 83 of 596 patients (13.9%) had measurable NAbs. The probability of developing NAbs increased with the single and cumulative dose of treatment and was influenced by the BoNT/A formulation, while all other factors analyzed, including disease entity and treatment duration, had no additional influence. Conclusions: We present the largest study to date of the prevalence of BoNT/A NAbs in a large unbiased cohort of patients including the relevant neurologic indications. Repeated injections of BoNT/A inevitably bear the risk of developing NAbs. However, in addition to avoiding booster injections and providing short intervals between injections, reducing the individual injected doses may diminish the risk of NAb induction independently of the indication for which BoNT/A is used.